Confirmation of linkage of hyperkalaemic periodic paralysis to chromosome 17. Issue 9 (September 1991) - Koch, M C; Ricker, K; Otto, M; Grimm, T; Hoffman, E P; Rüdel, R; Bender, K; Zoll, B; Harper, P S; Lehmann-Horn, F
Abstract : Linkage studies were performed in six European families with hyperkalaemic periodic paralysis (PPII) with myotonia, an autosomal dominantly inherited disorder characterised by episodic weakness. The weakness is caused by non-inactivating sodium channels of reduced single channel conductance of the muscle fibre membrane. Recently, portions of the gene coding for the alpha subunit of the sodium channel of the adult human skeletal muscle (h-Na2) have been cloned and localised on chromosome 17q with no recombinants to the human growth hormone locus (GH1). Linkage between these two chromosome 17 markers and the disease was shown in our families (Z = 7.14, 0 = 0.00). These results, combined with the linkage data of a single large American family, suggest that the disease is caused by dominant mutations of the adult sodium channel, and that it is probably a genetically homogeneous disorder. Hyperkalaemic periodic paralysis is the first non-progressive myotonic disorder to be localised on the human genome.